Interior miniature models its relevance with the development and presentation of design concepts - Uy, Sidney Siy; Florendo Raquel Baltazar (1992.)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Research paper (ID 199)--University of the Philippines Diliman.
Title from cover.
Keywords: Architectural models; Miniature objects